A pairwise comparison-based interactive procedure for the process capability approach to multiple-response surface optimization. Issue 10 (2nd October 2020) - Jeong, In-Jun; Lee, Dong-Hee
Abstract : Multiple-response surface optimization (MRSO) aims to find a setting of the input variables that simultaneously optimizes the multiple responses. The process capability approach incorporates a decision maker's (DM's) preference information in the problem-solving process while considering the dispersion effects of the responses systematically through the framework of the process capability index. However, the existing process capability methods are based on an unrealistic assumption that all the preference information of the DM is given in advance. Although a few methods incorporate the DM's preference information while solving the problem, they require too much preference information from the DM. In this article, a new interactive capability method, the pairwise comparison-based interactive process capability approach (PC-IPCA), is proposed to alleviate the DM's burden in the solving process. The proposed method is illustrated through a well-known MRSO problem. The advantages of the proposed method compared with existing process capability methods are discussed.